Reshaping Urbanization in Rwanda : Urbanization, Job Creation, and Poverty Reduction in Rwanda - World Bank Group (World Bank, Washington, DC, 2017)
This note analyzes whether and how the country’s rising urbanization levels (measured primarily by population density) are associated with nonfarm job creation and poverty reduction. By focusing on Rwanda’s 416 geographic sectors for the decade from 2002 and 2012, the analysis shows that, overall, a 10 percent increase in population density at the geographic sector level was associated with a 1.2 percent lower multidimensional poverty index and 1.4 point higher share of nonfarm employment. These linkages are estimated to be stronger in the areas with higher population density as of 2002, were closer to Kigali, and/or had better market access. Although increasing population density was profoundly associated with poverty reduction and job creation in secondary cities and areas within a five‐kilometer radius, those linkages are less clear in areas beyond five kilometers from the city cores. The finding highlights the importance of extending economic opportunities to the poor living in the outer areas of secondary cities, which accounts for a third of the country’s poor population. This Note also finds that fewer farmers are poor where fewer nonfarm workers are in poverty in the same areas or surrounding areas, and the latter points to spillover effects.